Beyond the Ivory Tower: A Study of Germany's Dual System of Higher Education - Yuan-Chuan Chang (National Taipei University of Education, 2017)
In this paper, document analysis was used to investigate the Germany's dual system of higher education. Notable examples include the models of Baden-Württemberg, Nordrhein-Westfalen and Bayer. Students in this system of education can satisfy the demands of industry; the job prospects of graduates has been enhanced where 85 percent of those who graduate from Baden-Wuerttemberg Cooperative State University found work in their field prior to graduation. For a long time, there has been a distance between higher education and the realities of the wider society; however, due to recent developments in modern times, academia is becoming more relevant and connected to the society as a whole. As a result, a close relationship has been developed between university education and vocational education. This relationship is based not only on the needs of the society, but also on changes in epistemology, the rise of the competition state, and the difficulties arising from the gap between what students learn at universities and the actual needs of the industry. Germany's dual system of higher education is seen as a paragon. By contrast, in Taiwan there remains a large gap between what students learn at universities and the actual needs of the industry, resulting in an imbalance of supply and demand in the labor market. Thus the educational authorities in Taiwan may consider the applicability of adopting the German system of dual education.